Social interactions that support students' self-regulated learning: A case study of one teacher's experiences. (2015) - Alvi, Effat; Gillies, Robyn M.
Highlights: We present a case study of an experienced, Grade 7 teacher. We explore how she (the case) supports students' SRL through social interactions. We identify sub-processes involved in developing SRL through social interactions. The outcomes are a valuable starting point for future research. Abstract: Developing self-regulated learning (SRL) among students is critically important to enable success in and beyond school. This case study highlights the practices of an experienced Grade 7 teacher, Janet (pseudonym), who supported students' SRL through social interactions. This exemplary case was drawn through a screening procedure with data collected via an in-depth interview, informal conversations, and classroom observations. The study presents the teacher's perspective and ways of working to support students' SRL. The data reveals that constructive social interactions and SRL are closely linked. The implications are discussed in light of SRL supportive teaching practices.